Which farms drill during drought? The influence of farm size and crop type. Issue 2 (4th March 2022) - Reisman, Emily; Macaulay, Luke
ABSTRACT: Excessive groundwater extraction is exacerbated by worsening droughts under climate change. Among agricultural users, well-drilling activity is not evenly distributed. The number, diameter and depth of new agricultural wells were analysed in this study in relation to farm size and land cover class during California's 2012–16 extreme drought. The results show smaller farms drilled at higher rates, whereas larger farms drilled at comparatively greater depths and with wider wellbores. Sections dominated by permanent crops drilled at 2.4 times the rate of those dominated by annual crops, and at 24.7 times the rate of forest and rangeland dominated sections.